Community, River and Basin: Watersheds in Northern Sarawak as a Social Linkage - Jayl, Langub; Noboru, Ishikawa (Springer Singapore, 2017)
How have distant people living in separate river systems historically maintained contact? What are the factors contributing to the consolidation of their social relationships and networks? By answering these questions, our ethnographic inquiry on northern Sarawak elucidates key features of the cultural, socioeconomic and geomorphological characteristics of Borneo. To examine social formations in a riverine basin, we focus on watershed pathways, or the connecting points between two or more riverine catchments. In doing so, we attempt to separate ourselves from previous studies on migration. First, we look at the social formation from trans- as well as multiethnic perspectives, comprehensively examining more than two dozen ethnic groups and their interrelations. The second vantage point is that we map migratory movements in a wider spatial arena of Sarawak than has previously been studied. The unit of analysis is a vast basin society located in a triangular area carved out by the South China Sea, the Rejang and the Baram rivers. Third, we pay attention to geomorphological features of the basin society. Distance, elevation and connectivity provide the most crucial factors to consider when investigating the formation of Bornean riverine society.